Correlation Between Company’s Lock Out Tag Out (LOTO) System with LOTO Implementation Behavior of Mechanic in Plant Department - Hapsari, A; Erwandi, D; Ardyanto, Y D (KnE Life Sciences, 2018)
Lock Out Tag Out (LOTO) is a system of locking and labeling on an energy source of isolation equipment. LOTO aims to protect mechanics on maintaining and servicing. Application of Lock Out Tag Out is influenced by behavior. This study aimed to analyze the correlation of LOTO system that has been implemented in the company, involving the LOTO training, supervision, and reward and punishment with the LOTO implementation behavior of mechanics. This research was observational with crosssectional study. Samples were 50 respondents taken by simple random sampling with a population of 97 mechanics. Data were analyzed statistically using Chi Square test (α <0.05) and continued by observed value of phi coefficient. The results showed that most of the mechanics in the Plant Department of PT. X (mining company) had implemented LOTO in every maintaining and servicing equipment well. Statistical analysis showed the variables have a significant correlation with LOTO application on mechanics was supervision (sig = 0.047; phi value = 0.312). LOTO training, reward, and punishment did not have significant correlation with LOTO application. In conclusion, supervision had significant correlation with LOTO implementation on mechanics. The mining company should increase transfer knowledge to mechanics by putting LOTO signs around workshop area, increasing supervising role of the foreman and OSHE Department, making a LOTO training and refresh training schedule and evaluating it, and also giving rewards to mechanics regularly. Keywords: Lock Out Tag Out (LOTO), mechanic, mining company